Metal-phenolic encapsulation of carbon monoxide releasing molecule for enhanced gas therapy of periodontitis - Caiye Liu; Yi Chen; Ying Wang; Danyang Wang; Jinyan Sun; Jiao Sun; Lingli Ji; Kai Li; Wenjun Wang; Weiwei Zhao; Hui Song; Jianhua Li (Materials Today Bio)
Periodontitis is an infectious disease caused by plaque-associated microorganisms. The condition is characterized by the activation of oxidative stress and immune responses, which contribute to tissue destruction. Carbon monoxide (CO)-based gas therapy, utilizing CO releasing molecules (CORMs), presents a promising therapeutic strategy; however, its efficacy is constrained by the short half-life and limited cellular uptake of CORMs. In this study, metal-phenolic networks (MPN) were employed as a carrier to stabilize CORMs via metal-ligand coordination, thereby forming a nanocomplex designated as CO@MPN. This nanocomplex demonstrated effective scavenging of reactive oxygen species (ROS) and exhibited ROS-responsive CO release. Following phagocytosis by macrophages, CO@MPN significantly decreased intracellular ROS levels, reduced the production of inflammatory factors in lipopolysaccharide (LPS)-stimulated macrophages, facilitated macrophage polarization towards the anti-inflammatory M2 phenotype, and activated heme oxygenase-1 (HO-1) to further attenuate inflammation. In murine models of experimental periodontitis, CO@MPN significantly inhibited inflammatory bone loss and exerted macrophage-regulating effects. The findings underscore the potential of ROS-responsive CO gas therapy as a promising strategy for the treatment of periodontitis and the management of other inflammatory diseases.